2019
DOI: 10.3390/molecules24152834
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of the RELA Gene is Associated with Expression of NF-κB1 in Response to TNF-α in Breast Cancer

Abstract: The nuclear factor (NF)-κB family of transcriptional factors plays a critical role in inflammation, immunoregulation, cell differentiation, and tumorigenesis. This study aims to investigate the role of methylation of genes encoding for the NF-κB family in breast cancer. We analyze the DNA methylation status of the NFKB1 gene and the RELA gene in breast cancer using pyrosequencing. The expression of NF-κB1 and RELA proteins is assessed and the level of RNA transcripts in frozen tissue is determined using RT-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Additionally, MAPK1 affects the progression of breast and ovarian cancers by participating in multiple signalling pathways [ 45 , 46 ], and AKT1 is closely related to cancer and a variety of diseases through its roles in metabolic regulation and signalling pathways [ 47 , 48 ]. RELA is an important target gene in NF- κ B signalling; Lu and Yarbrough [ 49 ] reported that RELA dephosphorylation inhibits tumour development [ 49 ], and other studies have indicated that RELA methylation and subsequent activation of multiple downstream genes contribute to the regulation of breast cancer progression [ 50 , 51 ]. JUN is an activator protein-1 transcription factor subunit that regulates the expression of multiple genes critical to cell proliferation, differentiation, and apoptosis [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, MAPK1 affects the progression of breast and ovarian cancers by participating in multiple signalling pathways [ 45 , 46 ], and AKT1 is closely related to cancer and a variety of diseases through its roles in metabolic regulation and signalling pathways [ 47 , 48 ]. RELA is an important target gene in NF- κ B signalling; Lu and Yarbrough [ 49 ] reported that RELA dephosphorylation inhibits tumour development [ 49 ], and other studies have indicated that RELA methylation and subsequent activation of multiple downstream genes contribute to the regulation of breast cancer progression [ 50 , 51 ]. JUN is an activator protein-1 transcription factor subunit that regulates the expression of multiple genes critical to cell proliferation, differentiation, and apoptosis [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Group A associators overpowered the epigenetic link to group B interactors. RELA has shown an increased methylation level that is significant in the progression of breast cancer [ 47 ], HMOX2 has shown an increased hypomethylation in endometriosis [ 48 ], while EZH2 mediates histone modification H3K27m3 and causes several cancers [ 49 ]. ERRFI1 is discerned to have an epigenetic downregulation in neuroblastoma tumors [ 50 ], and WDR1 has been shown to get overexpressed in non-small cell lung cancer (NSCLC) [ 51 ], whereas, p10Y-ERBB3-1 is discerned to have shown histone methylation of H3K27m3 in general [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…This evidence suggests that since the majority of the network associators of POTEE are epigenetically activated in many cancers, it is quite natural for POTEE paralog to get over-expressed and epigenetically regulated in ovarian cancer too. Moreover, there exist various experimental studies [ 19 , 20 , 44 ], [ 45 ], [ 46 ], [ 47 ], [ 48 ], [ 49 ], [ 50 ], [ 51 ], [ 52 ], [ 53 ], [ 54 ] that discern its epigenetic dynamics in different diseases.…”
Section: Resultsmentioning
confidence: 99%
“…NF-κB consists of NFKB1 or NFKB2 combined with REL, RELA or RELB. NFKB1 compounded with the gene product RELA is the most extensive form [ 44 , 45 ]. For rheumatoid arthritis, Sabir's study used a weighted gene co-expression network to analyze the function of the NF-κB protein family and its regulators, and proved that these genes (such as NFKB2) may be involved in the inflammation and immune pathogenesis of rheumatoid arthritis with an important role [ 46 ].…”
Section: Discussionmentioning
confidence: 99%